Numerical and experimental study on the response of multi-walled carbon nanotube/polymer composites under compressive loading. (1st January 2013) - Takeda, T.; Narita, F.; Kuronuma, Y.; Shindo, Y.
In this paper, we present the numerical and experimental characterisation of the compressive behaviour of multi-walled carbon nanotube (MWNT)/polymer composites. Compression tests were conducted on MWNT/ polymer composites at room temperature and liquid nitrogen temperature (77 K) to identify the effect of nanotube addition on their macroscopic behaviour. Multiscale analysis was also performed to predict the composite response to compressive loading. Three-dimensional finite elements were used to model the representative volume element (RVE) of MWNT/polymer composites, and the nanoscale structure of the MWNT was incorporated by determining its elastic properties using analytical molecular structural mechanics models. It was found that the elastic modulus in compression is improved effectively by adding MWNTs. The correlation between the numerical and experimental results presents some basic insights regarding the reinforcing mechanisms in the nanocomposites under compression.